Strategi Pengembangan Proyek Lembaga Pendidikan Islam di Madrasah Al-Jam’iyatul Washliyah Tembung - Inom Nasution; Handoko Handoko; Riswan Hadi; Rosida Hanum; Amar Tarmizi; Hamdan Hamdan (Journal on Education, 2023)
This study aims to obtain an overview of the development strategy of Islamic education institutions at Madrasah Tsanawiyah Al-Jam’iyatul Washliyah Tembung which includes: a) Explanation of what internal and external factors influence development b) Explanation of the development strategy formulation process, c) Explanation of how the development strategy is implemented, and d) Description of how to evaluate and control the development strategy. The research method used in this research is qualitative with a case study model. The results of the research are then presented in descriptive form. Data collection in this study was carried out by means of observation, a document study, in-depth interviews, and data triangulation. The results of this study indicate that Madrasah Tsanawiyah Al-Jam’iyatul Washliyah Tembung has successfully implemented a development strategy. The development strategy is carried out on the development of financing, facilities, and infrastructure, as well as the quality of graduates and student achievement. The results of the SPACE analysis produce a position of Strengths Opportunities (aggressive strategy), namely a strategy to take advantage of opportunities by using the strengths of the school. The results of the SWOT analysis resulted in alternative strategies, namely (a) developing market segments with clear and firm policy directions, (b) developing school infrastructure by opening networks and collaborating with other institutions (banks, companies, and government), (c) developing business schools in Educational Institution-Owned.